KONSEP SULŪK ‘ABD AL- ṢAMAD AL-FALIMBĀNĪ: STUDI KITAB SIYAR AL-SĀLIKĪN FĪ ṬARĪQAH AL-SĀDĀT AL-ṢŪFIYAH - Ahmad Bagus Kazhimi (Ushuluna: Jurnal Ilmu Ushuluddin, 2020)
This article discusses the concept of sulūk, ‘Abd al-Ṣamad al-Falimbānī's book, "Siyar al-Sālikīn fi Ṭarīqah al-Sādāt al-Ṣūfiyah." Using a descriptive analytic method, this study answers the question of "how is the concept of sulūk according to  al-Falimbānī?". It finds that  sulūk is important and valuable in Nusantara  knowledge heritage, mainly in sufism. It also finds that the concept of sulūk of al-Falimbānī is considered as an important key for a sālik in making his way to Allah SWT. However, al-Falimbānī does not provide detail information about  wirid, or similar aspects which should be performed by sālik in his daily life